Microsoft Office 2003 in 10 Simple Steps or Less - Desmond, Michael (Wiley Publishing, 2011)
If you are looking to perform specific activities in Microsoft Office 2003 fast, then this book is for you-whether you're new to Microsoft Office or you're just upgrading to the 2003 version. This comprehensive guide delivers the answers you need with clear, easy-to-follow instructions for more than 250 key Microsoft Office 2003 tasks that cover everything from adding formulas in Excel to managing contacts in Outlook to graphing data and building presentations. Each task is presented in ten quick steps-or less-on easy-to-navigate pages, with lots of screen shots and to-the-point directions to guide you through every common (and not so common) Microsoft Office 2003 challenge-and help you get more done in less time. * Each solution is ten steps-or less-to help you get the job done fast * Self-contained two-page spreads deliver the answers you need-without flipping pages * A no-fluff approach focuses on helping you achieve results * A resource packed with useful and fun ways to get the most out of Microsoft Office 2003